HUBUNGAN ANTARA MINAT BELAJAR DAN KETERAMPILAN MEMBACA DENGAN HASIL BELAJAR BAHASA INDONESIA - Ijah Sopiah (Akademika, 2015)
The objective of the research is to find out the relationships between learning interestand reading skill with the learning outcomes in Indonesian language at the class sixprimary and secondary school in district Cimanggis, Depok. The study was designed as asurvey. Eighty four students, that were randomly selected, were involved in the study.Simple and multiple regression and correlation procedures were used in the data analysis.The results of the study pointed out that : (1) there was a positive relationship betweenlearning interest with the learning outcomes in Indonesian language , (2) there was apositive relationship between skill reading with the learning outcomes in Indonesianlanguage, and (3) ) there was a positive relationship between learning interest and skillreading with the learning outcomes in Indonesian language.Therefore, it could be concluded that the higher learning interest and reading skill, thehigher learning outcomes in Indonesian language.